A novel cytotoxic anti-B7-H3 affibody with therapeutic potential in acute myeloid leukemia - Vasilescu, Andrei-Mihai; Vasilescu, Adina-Gabriela; Sima, Livia Elena; Munteanu, Cristian V. A.; Baran, Natalia; Szedlacsek, Ștefan-Eugen (Frontiers in Pharmacology, 2025)
IntroductionAcute Myeloid Leukemia (AML) is a group of very aggressive hematological malignancies, with dismal long-term survival rates and little therapeutic recourse presently. The transmembrane ligand B7-H3 is a known therapeutic target, biomarker of response and correlated with an unfavorable prognosis in several malignancies, including AML, due to acquired resistance to immune checkpoint-targeting therapies. Therefore, developing therapeutic strategies with improved efficacy to overcome this obstacle constitutes an unmet need. Our study entails the design, production and in vitro testing of a novel recombinant Affibody with high affinity for B7-H3 coupled with the cytotoxic peptide Magainin-2, known for its membranolytic properties and potent antimicrobial and antitumor activity.MethodsWe expressed the conjugate in Escherichia coli, affinity purified it and confirmed its sequence by nanoLC-MS/MS. B7-H3-positive AML representative THP-1 cells and B7-H3-negative B-lymphoblastic RAJI cells were used for the experiments. The IC50 of the cytotoxic conjugate was determined through MTS assay and its necrotic, apoptotic and antiproliferative activities were evaluated by flow cytometry and Western blot.ResultsOverall, the results show that our cytotoxic anti-B7-H3 affibody possesses strong antiproliferative and cell death-inducing activity that is highly specific to B7-H3-expressing AML cells (IC50 against THP-1 cells was 26.35 µM). Moreover, this observed activity of our conjugate is significantly more potent than the previously described activity of Magainin-2 alone.ConclusionIn conclusion, we designed, produced and evaluated a novel anti-B7-H3 cytotoxic affibody-drug conjugate (AfDC) that, from these preliminary in vitro data, shows high potential for translation to the therapy of AML, warranting further preclinical and translational exploration, including pharmacokinetic and in vivo efficacy studies.